Enhancing Medical Image Security through Dual Cryptographic Paradigms: AES Symmetric Encryption and ECC Asymmetric Key Cryptography - A, Hambali Moshood; A, Olasupo Yunusa; Shehu, Umar (Darul Yasin Al Sys, 2024)
The rapid advancements in medical imaging technologies have highlighted the urgent need for secure transmission methods to protect patient confidentiality and ensure data integrity. This study presents a hybrid encryption approach that integrates Elliptic Curve Cryptography (ECC) with the Advanced Encryption Standard (AES) to effectively encrypt and decrypt medical images. The research methodology includes dataset collection, the development of AES and ECC algorithms using the Tkinter GUI, and performance assessments. AES utilizes a 128-bit key length, allowing for quick encryption and decryption, while ECC enhances security through the use of a public-private key pair. The performance evaluation focuses on throughput in relation to image size and the time taken for encryption and decryption. This research work enhances data security in healthcare by providing a reliable and efficient model for the encryption and decryption of medical images.